أثر عضوية المرأة في مجلس الإدارة على العلاقة بين مستوى الإفصاح عن المخاطر وقيمة الشركة بالتطبيق على الشركات المقيدة بالبورصة المصرية - الملاح، شيرين شوقي السيد; عبدالفتاح، هبة بشير الطوخي (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
The objective of the research: to analyze the impact of women's membership in the board of directors on the relationship between the risk disclosure level and the firm value. design and methodology: an applied study was conducted on a sample of (131) companies using the content analysis method in examining the annual reports of companies during the period from 2019 to 2023 with a total of (655) views to test the research hypotheses that reflect the impact of women’s membership in the board of directors on the relationship between the risk disclosure level and the firm value. the multiple regression method and sensitivity analysis method were also used to test the results. women's membership in the board of directors was measured by dividing the number of female members in the board of directors by the total number of male and female board members. the risk disclosure level was measured depending on two indicators: the risk disclosure coverage for financial and non-financial risks and the quantity of risk disclosure. the firm value was measured using the Tobin’s Q index. results and recommendations: the low level of risk disclosure for the sample companies, whether in terms of risk disclosure coverage for both financial and non-financial risks or the amount of risk disclosure, as well as the interest of these companies in disclosing the financial risks and not disclosing most of the non-financial risks. there is a significant effect of women’s membership in the board of directors on risk disclosure coverage and risk disclosure quantity, and there is a significant effect of women’s membership in the board of directors on firm value. while there is also a significant effect of the risk disclosure level (using risk disclosure coverage and risk disclosure quantity indicators) on the firm value. finally, there is a significant effect of women’s membership in the board of directors on the relationship between the risk disclosure level and the firm value. accordingly, the study recommends the necessity of gender diversity in the board of directors, in addition to encouraging companies to attract female competencies to the board of directors, as the presence of women is based on their experience and competence, as well as directing companies’ attention to improve and increase the level of risk disclosure in annual reports, which results in increasing the firm value. originality and addition: the current research provides a contribution and addition to the current researches in this field by attempting to propose an index to measure the level of risk disclosure and also the impact of the percentage of women’s presence on the board of directors on the relationship between the level of risk disclosure and the firm value. هدف البحث: تحليل أثر عضوية المرأة في مجلس الإدارة على العلاقة بين مستوى الإفصاح عن المخاطر وقيمة الشركة. التصميم والمنهجية: تم إجراء دراسة تطبيقية على عينة مكونة من (131) شركة باستخدام أسلوب تحليل المحتوى في فحص التقارير السنوية للشركات خلال الفترة من عام 2019 حتى عام 2023 بإجمالي مشاهدات (655) مشاهدة لاختبار فروض البحث التي تعكس أثر عضوية المرأة في مجلس الإدارة على العلاقة بين مستوى الإفصاح عن المخاطر وقيمة الشركة، كما تم استخدام أسلوب الانحدار المتعدد وأسلوب تحليل الحساسية في اختبار النتائج، وتم قياس عضوية المرأة في مجلس الإدارة عن طريق قسمة عدد الأعضاء الإناث في مجلس الإدارة على إجمالي عدد أعضاء مجلس الإدارة من الذكور والإناث، وتم قياس مستوى الإفصاح عن المخاطر اعتمادا على مؤشرين تتمثل في مدى تغطية الإفصاح عن المخاطر في التقارير المالية السنوية لكافة المخاطر المالية وغير المالية وكمية الإفصاح عن المخاطر، أما قيمة الشركة فقد تم قياسها باستخدام مؤشر Tobin’s Q. النتائج والتوصيات: انخفاض مستوى الإفصاح عن المخاطر لشركات العينة سواء فيما يتعلق بمدى تغطية الإفصاح عن المخاطر لكلا من المخاطر المالية وغير المالية أو كمية الإفصاح عن المخاطر، وكذلك اهتمام تلك الشركات بالإفصاح عن المخاطر المالية التي قد تتعرض لها الشركة وعدم الإفصاح عن معظم المخاطر غير المالية، ويوجد تأثير معنوي لعضوية المرأة في مجلس الإدارة على كلا من تغطية وكمية الإفصاح عن المخاطر، كما يوجد تأثير معنوي لعضوية المرأة في مجلس الإدارة على قيمة الشركة، في حين يوجد تأثير معنوي لمستوى الإفصاح عن المخاطر مقاسا بالتغطية والكمية على قيمة الشركة، وأخيرا يوجد تأثير معنوي لعضوية المرأة في مجلس الإدارة على العلاقة بين مستوى الإفصاح عن المخاطر وقيمة الشركة، واستنادا إلى ذلك توصى الدراسة بضرورة التنوع بين الجنسين في مجلس الإدارة بالإضافة إلى تشجيع الشركات على استقطاب الكفاءات النسائية في عضوية مجلس الإدارة بحيث يكون تواجد المرأة بناء على خبرتها وكفاءتها، وكذلك توجيه اهتمام الشركات بتحسين وزيادة مستوى الإفصاح عن المخاطر بالتقارير السنوية لما يترتب عليه من ارتفاع قيمة الشركة. الأصالة والإضافة: يقدم البحث الحالي مساهمة وإضافة للبحوث الحالية في هذا المجال من خلال محاولة اقتراح مؤشر لقياس مستوى الإفصاح عن المخاطر وتأثر العلاقة بين مستوى الإفصاح عن المخاطر وقيمة الشركة بنسبة وجود المرأة في مجلس الإدارة.